Molecular and serological detection of Ehrlichia canis and Babesia vogeli in dogs in Colombia (2012)
Ehrlichiosis and babesiosis are tick-borne diseases, caused mainly by Ehrlichia canis and Babesia canis, respectively, with a worldwide occurrence in dogs, whose main vector is the brown-dog tick, Rhipicephalus sanguineus. The present work aimed to detect the presence of E. canis and Babesia sp. in 91 dog blood samples in Colombia, by molecular and serological techniques. We also performed sequence alignment to indicate the identity of the parasite species infecting these animals. The present work shows the first molecular detection of E. canis and B. vogeli in dogs from Colombia. Immunoglobulin-G (IgG) antibodies to E. canis and Babesia vogeli were found in 75 (82.4%) and 47 (51.6%) sampled dogs, respectively. Thirty-seven (40.6%) and 5 (5.5%) dogs were positive in PCR for E. canis and Babesia sp., respectively. After sequencing, amplicons showed 99% of identity with isolates of E. canis and B. vogeli. The phylogenetic trees based on 16S rRNA-Anaplasmataceae sequences and 18S rRNA-piroplasmid sequences supported the identity of the found E. canis and B. vogeli DNAs, respectively. The present work shows the first molecular detection of E. canis and B. vogeli in dogs in Colombia. © 2011 Elsevier B.V.